Inquiry in the development of critical thinking in 5-year-old infants - Fernández Otoya, Fiorela Anaí; Gallardo Yrigoín, Brisaida; Sánchez-Chero, Manuel Jesús; Collazos Alarcó, Mercedes Alejandrina; Arias-Chávez, Dennis (Journal of the University of Zulia, 2021)
The objective of the study is to determine the influence of the Program based on inquiry projects on the development of Critical Thinking in infants. The methodology used is quantitative, applied type, of quasi-experimental design. The participants were 100 infants, 5-year-old, distributed in the experimental (n=50) and control (n = 50) groups. The results of the pre-test showed that all infants were at the starting level; while, in the post -test, the experimental group had a significant improvement, with 66% in expected achievement, 24% in process and 10% in outstanding achievement; whereas, those of the control group reached the beginning level, in process and expected achievement levels with 18, 74 and 8% respectively. It was determine that the program based on inquiry projects had a significant influence on the development of critical thinking in infants, improving their capacity for argumentation, problem solving and metacognition.